High acuity polytrauma centers in orthopaedic trauma: Decreasing patient mortality with effective resource utilization. Issue 10 (October 2020) - Schwartz, Andrew M.; Staley, Christopher A.; Wilson, Jacob M.; Reisman, William M.; Schenker, Mara L.
Highlights: High acuity polytrauma centers are defined as the upper 50 th percentile of annual admissions of polytrauma patients with ISS>15. These centers have a decreased mortality for severely injured patients when compared to low acuity trauma centers. The same mortality benefit was not seen when comparing American College of Surgeons designated level one trauma centers to other institutions. High acuity centers have greater rates of perioperative complications and resource utilization. The difference in complications and resource utilization becomes nondifferent when correcting for injury severity. Abstract: Background: There is a select number of massive-volume, high-acuity trauma centers (HACs) in the United States. Expertise in polytrauma care has been associated with improved mortality in general surgery trauma, though has not been investigated in orthopaedic trauma. With complex polytrauma proficiency comes the inherent risk of intensive care, complications, and prolonged inpatient stays, without a commensurate increase in allocated resources. The purpose of this study was to compare mortality, complications, and length of stay in polytraumatized orthopaedic patients treated at HACs vs. low-acuity trauma centers (LACs). Methods: The National Trauma Data Bank was queried for orthopaedic injuries with injury severity score (ISS)>15 and mortality, complications, hospital length of stay, ICU length of stay, ventilation duration, and demographics. Hospitals where at least 13% (median percentage of patients with ISS > 15 admitted to all hospitals) of total admissions had an ISS>15 were classified as HAC; all others were LACs. Results: HACs admitted 86.8% of 28, 314 patients with ISS>15. On univariate analysis, patients at HACs have 16% decreased odds of in-hospital mortality vs. LACs (p=0.005); the effect increased to 27% (p=0.002) on multivariate analysis. Patients at HACs have 63% greater odds of ICU admission (p<0.001), 48% higher odds of ventilatory support (p=<0.001), 38% increased odds of unplanned reoperation (p=0.007), and 37% increased odds of medical complications (p<0.001). On multivariate analysis, secondary outcome measures showed no significant difference between HACs and LACs. Patients at HACs had 2.8 days longer length-of-stay (p<0.001). Conclusion: Severely injured orthopaedic trauma patients have decreased mortality at HACs, despite having a higher average ISS and a higher prevalence of obesity and active smoking. While there is a higher incidence of ICU admission, mechanical ventilation, complications, and unplanned reoperation on univariate analysis, correction for ISS and patient factors enhances the effect of HACs on mortality, but removes the effect on secondary measures. Thus, HACs are life-saving institutions for polytraumatized orthopaedic patients, and the known resource demand of these hospitals is supported by their favorable outcome profile. Level of evidence: IV